The effect of vitamin D on the development of Hashimoto's disease and the reduction of the inflammatory process in its course - review - Elias, Jagoda; Woźniak, Justyna; Womperski, Karol; Szymonik, Julia; Szopa, Sebastian (Quality in Sport, 2024)
Introduction Hashimoto's disease is an autoimmune chronic lymphocytic thyroiditis. It is a common condition, more frequent in women. Its diagnosis is based on the presence of specific antithyroid antibodies in the patient's blood which lead to the destruction of the thyroid gland. This can result in the development of hypothyroidism, requiring levothyroxine replacement therapy. Aim of the review A summary of the information gathered so far on the involvement of vitamin D in the development and course of Hashimoto's disease. Results The articles analyzed have mixed results. Most of them show a positive correlation between vitamin D and Hashimoto's disease, paying particular attention to the contribution of vitamin D in moderating the inflammatory process in HT. Other studies show significant differences in vitamin D levels between groups with different HT severity. Others show a negative correlation between vitamin D levels and the development of Hashimoto's disease. Conclusions Large well-controlled randomized double blind trials are needed in order to determine the exact role of vitamin D in Hashimoto’s disease.